Functional identification of the calcineurin B-like protein PavCBL4 in modulating salt tolerance in sweet cherry - Fu, Quanjuan; Hou, Sen; Gao, Rui; Wei, Guoqin; Sun, Yugang (Frontiers in Plant Science, 2023)
Abiotic stresses, such as high salinity, pose a significant threat to plant growth and development, reducing crop yield and quality. Calcineurin B-like (CBL) proteins serve as crucial calcium sensors in plant responses to diverse environmental stresses.However, the CBL family in sweet cherry has not been identified at the genome-wide level, and the regulatory role of CBL proteins in cherry plants' salt response is unclear.Here, we identified 10 CBL family genes (PavCBLs) from the Prunus avium genome and cloned seven of them. We comprehensively analyzed PavCBL genes for collinearity, phylogenetic relationships, gene structure, and conserved motifs. Expression analysis revealed significant induction of transcription under abiotic stress, with PavCBL4 displaying the most substantial expression change. Additionally, we identified PavCBL4 as a PavSOS2 (Salt Overly Sensitive 2)-interacting protein through Y2H and Split-LUC assays. Subcellular localization analysis indicated that PavCBL4 is present in both the cytoplasm and nucleus. Functional assessment of PavCBL4 in the PavCBL4-overexpressing transgenic 'Gisela 6' plants showed its positive role in enhancing salt tolerance in cherry plants. Measurements of Na + content and antioxidant enzyme activity under salt stress indicated that PavCBL4 functions positively by inhibiting Na + accumulation and promoting ROS scavenging in response to salt stress. These findings lay the groundwork for a deeper understanding of the molecular mechanisms underlying PavCBL-mediated salt tolerance in sweet cherry.